Livskvalitet i familier: nære relasjoners betydning for ”det gode liv” (Sociologisk Forskning, 2007)
Life quality in families: close relations and “the good life”The aim of this paper is to explore how aspects and qualities of modern family life influence subjective well-being. Although the patterns of family, work and sexuality have changed dramatically the last four decades, it is here claimed that the family is still an important base of socialization and upbringing. Thus the study of processes within the family can contribute to the understanding of the environment in which many children grow up. In most families, work, partner and family roles are intertwined, and one central hypothesis of this work is that family members influence each other in the individual formation of well-being. The main research question of this study asks: How is life quality affected by the quality of parent-child and the partner relationships and aspects of their shared everyday life? Empirical implications are tested against 2002-data from a representative, Norwegian sample. Analyses conclude that the quality of parent-child and the spousal relationship, and also aspects of families’ everyday life such as work-life balance and time pressure influence the subjective life quality, but mother’s and father’s life quality is affected by differing and partly incompatible conditions.
Keywords: family; life quality; close relations; work-life balance